Knufia aspidiotus sp. nov., a new black yeast from scale insects - He, Fan; Lin, Bin; Sun, Jingzu; Liu, Xingzhong (Phytotaxa, 2013)
Three ascomycetes, isolated from the body cavity of the scale insect, Aspidiotus sp., collected in Song Mountain, Yanqing, Beijing, China, were identified to be a new species of Knufia. Knufia aspidiotus sp. nov. is introduced in this paper. The species is characterized by slow-growing, dematiaceous and blastic, endogenous conidia in undifferentiated hyphae, as well as darkly pigmented, enlarged multicellular bodies, and is similar to other Knufia species in morphology. Phylogenetic analyses, based on the small ribosomal subunit (SSU) gene and internal transcribed spacer (ITS) region, indicated that Knufia aspidiotus was related to, but clearly distant from other sequenced species in Knufia.